2019
DOI: 10.1038/s41401-019-0257-1
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine A ameliorates obesity-related cognitive performance impairments involving neuronal insulin signaling pathway in mice

Abstract: Type 2 diabetes (T2D) and Alzheimer’s disease (AD) share several common pathophysiological features. Huperzine A (Hup A), a Lycopodium alkaloid extracted from the Chinese herb moss Huperzia serrata , is a specific and reversible inhibitor of acetylcholinesterase, which is clinically used for the treatment of AD. In this study, we investigated whether Hup A improved the metabolic and cognitive functions in the high fat-induced (HFD) obese mice and genetic ob/ob mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
(77 reference statements)
0
13
0
1
Order By: Relevance
“…Similarly, in vivo studies showed that Lycopodium selago extract, administered to zebrafish (Danio rerio) with cognitive impairment caused by scopolamine, alleviates cognitive deficits, inter alia, by regulating ACHE activity [46]. Another study confirmed that treatment with HupA improved cognition in mice with diet-induced obesity [49]. Other studies showed that angelica polysaccharide ameliorates memory impairment in animal models of cognitive disorders, although the exact mechanisms have not yet been understood [50][51][52][53].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in vivo studies showed that Lycopodium selago extract, administered to zebrafish (Danio rerio) with cognitive impairment caused by scopolamine, alleviates cognitive deficits, inter alia, by regulating ACHE activity [46]. Another study confirmed that treatment with HupA improved cognition in mice with diet-induced obesity [49]. Other studies showed that angelica polysaccharide ameliorates memory impairment in animal models of cognitive disorders, although the exact mechanisms have not yet been understood [50][51][52][53].…”
Section: Discussionmentioning
confidence: 97%
“…Novel object recognition test (NORT) was carried out as described, with slight modification. 30,31 On the first day, each mouse was subjected to a 5-min trial to acclimatize to the arena (40 cm × 40 cm × 30 cm) without objects. Twenty-four hours after acclimatization session, each mouse was given 5 min to explore (defined as sniffing or touching) identical objects (F1 and F2), placed in fixed adjacent corners.…”
Section: Methodsmentioning
confidence: 99%
“…kamtschaticus (EFAD) and Huperzine A (Hup A) are both extracts of TCM, which can improve cerebral insulin resistance and cognitive impairment in AD animals. Both of them can increase Ach and decrease AchE and improve synaptic function ( 152 , 153 ). Polyphenol rich frankincense(BS) gum has been proven to have anti-inflammatory, anticancer and anti-apoptotic effects.…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…ACF treatment can significantly increase pIRS, PI3K, and pAkt, restrain GSK3β overactivation, thus reducing Aβ deposition ( 156 ). Catechins, proanthocyanidins A1, A2 in Lychee seed and Huperzine A can inhibit hyperphosphorylated Tau through A similar pathway ( 153 , 157 ). Ginseng has many active components against AD.…”
Section: Manuscript Formattingmentioning
confidence: 99%